Maxillary anterior segmental distraction osteogenesis to correct maxillary hypoplasia and dental crowding in cleft palate patients: a preliminary study - Liwen Qian; Yufen Qian; Wener Chen (BMC, 2023)
Abstract Background The aim of this study was to present comprehensive skeletal, dental and facial aesthetic outcomes and long-term stability of maxillary anterior segmental distraction osteogenesis (MASDO) for the treatment of maxillary hypoplasia in CLP. Materials and methods Six patients with maxillary hypoplasia treated with MASDO by a miniscrew assisted intraoral tooth-borne distractor were included. Cephalometric radiographs were obtained before distraction (T1), after the consolidation period (T2) and after orthodontic treatment or before orthognathic surgery (T3). Thirty-one cephalometric variables (12 skeletal, 9 dental, and 10 soft tissue variables) were used to evaluate changes in the dentofacial structures and the soft tissue profile. Friedman and Wilcoxon tests were applied to identify significant differences in hard and soft tissue changes during the T1-T2, T2-T3, and T1-T3 periods. Results All patients successfully underwent MASDO without serious complications. From T1 to T2, forward movements of ANS and A (FH ⊥ N-A, VRL-ANS and VRL-A) were significant (p < 0.05). Significant increases in SNA and ANB were noted. Significant upward movement of points ANS (CFH-ANS) and A (CFH-A) was observed (p < 0.05). After distraction, a significant decrease in overjet and an increase in overbite were obtained (p < 0.05). Anterior tipping of the upper incisors (U1/ANS-PNS and U1/SN) was observed (p < 0.05). The soft tissue points of Pn, Sn, Ss, and ls showed significant anterior movement (p < 0.05). In addition, a significant increase in the nasolabial angle was measured (p < 0.05). All of the above data showed no statistically significant changes between T2 and T3 (p > 0.05). Conclusion MASDO using a miniscrew assisted tooth-borne distractor presented significant maxillary advancement and favorable long-term stability in treating CLP patients with maxillary hypoplasia.